The medicinal chemistry of dengue virus - Behnam, Mira A. M.; Nitsche, Christoph; Boldescu, Veaceslav; Klein, Christian D. (Journal of medicinal chemistry, 2016)
The dengue virus and related ﬂaviviruses are an increasing global health threat. In this perspective, we comment on and review medicinal chemistry eﬀorts aimed at the prevention or treatment of dengue infections. We include target-based approaches aimed at viral or host factors and results from phenotypic screenings in cellular assay systems for viral replication. This perspective is limited to the discussion of results that provide explicit chemistry or structure−activity relationship (SAR), or appear to be of particular interest to the medicinal chemist for other reasons. The discovery and development eﬀorts discussed here may at least partially be extrapolated toward other emerging ﬂaviviral infections, such as West Nile virus. Therefore, this perspective, although not aimed at ﬂaviviruses in general, should also be able to provide an overview of the medicinal chemistry of these closely related infectious agents.
Gesehen am 05.05.2020